Analiza porównawcza jakości życia seniorów w wybranych krajach Unii Europejskiej - Sawicz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
For more than twenty years, the number of elderly people in Europe has been increasing. This process is called “the graying of the continent”. The aging of societies raises many problems of a medical, social and economic nature. On the other hand, the increase in the quality of life of seniors caused less spending on medical and social care. The article attempts to analyze the quality of life of seniors in selected countries of the European Union. The level of quality of life was examined in economic aspect. Particular attention is paid to the health of the population in selected EU country and the level of poverty. The article indicates countries with the highest quality of life of the elderly and countries in which the quality of life of seniors is low
Keywords: jakość życia; starość; zdrowie społeczeństwa; wskaźnik ubóstwa